2023
DOI: 10.21873/anticanres.16207
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course of Vitamin B12 Deficiency and Associated Risk Factors in Patients After Total Gastrectomy for Gastric Cancer

Abstract: Background/Aim: Patients are at-risk for vitamin B12 deficiency after total gastrectomy due to a lack of intrinsic factors. The aim of the study was to clarify the clinical course and risk factors for vitamin B12 deficiency after total gastrectomy for gastric cancer patients. Patients and Methods: Patients who underwent curative resection for gastric cancer were selected from the medical records of the Yokohama City University from 2000 to 2020. A logistic regression analysis was performed to identify risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In this study, older GCSs reported lower vitamin B12 levels than did younger GCSs. Vitamin B12 deficiency is a common late effect that occurs in 50% of individuals following gastrectomy [ 32 ]. Prolonged vitamin B12 deficiency can lead to various hematologic, neurological, and psychiatric disorders and increase the risk of cardiovascular disease [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, older GCSs reported lower vitamin B12 levels than did younger GCSs. Vitamin B12 deficiency is a common late effect that occurs in 50% of individuals following gastrectomy [ 32 ]. Prolonged vitamin B12 deficiency can lead to various hematologic, neurological, and psychiatric disorders and increase the risk of cardiovascular disease [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive vitamin B12 interventions are crucial from the start of treatment in older GCSs with low preoperative vitamin B12 levels, as they are more vulnerable to vitamin B12 deficiency after digital gastrectomy [ 35 ]. Older GCSs may require more intensive interventions to address vitamin B12 deficiency due to irreversible factors such as older age and having undergone a gastrectomy [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lowered serum vitamin B12 has been reported in people with atrophic gastritis [2,60], Crohn's disease [61][62][63], celiac disease [64], infection with H. pylori [65], gastric surgeries [66][67][68][69][70], and chronic treatment with proton pump inhibitors [71]. Up to 70% of patients who undergo gastrectomy may develop vitamin B12 deficiency 12-24 months after surgery if not supplemented with the vitamin [72,73].…”
Section: Vitamin B12 Deficiency In the Medical Literaturementioning
confidence: 99%
“…Lowered serum vitamin B12 has been reported in people with atrophic gastritis [2,60], Crohn's disease [61][62][63], celiac disease [64], infection with H. pylori [65], gastric surgeries [66][67][68][69][70], and chronic treatment with proton pump inhibitors [71]. Up to 70% of patients who undergo gastrectomy may develop vitamin B12 deficiency 12-24 months after surgery if not supplemented [72,73].…”
Section: Vitamin B12 Deficiency In the Medical Literaturementioning
confidence: 99%